Double hexagonal close‐packed structure revealed in a single colloidal crystal grain by Bragg rod analysis. (1st August 2014) - Meijer, J.‐M.; Shabalin, A.; Dronyak, R.; Yefanov, O. M.; Singer, A.; Kurta, R. P.; Lorenz, U.; Gorobstov, O.; Dzhigaev, D.; Gulden, J.; Byelov, D. V.; Zozulya, A. V.; et al.
Abstract : A coherent X‐ray diffraction study of a single colloidal crystal grain composed of silica spheres is reported. The diffraction data contain Bragg peaks and additional features in the form of Bragg rods, which are related to the stacking of the hexagonally close‐packed layers. The profile of the Bragg rod shows distinct intensity modulations which, under the specific experimental conditions used here, are directly related to the stacking sequence of the layers. Using a model for the scattered intensity along the Bragg rod for an exact stacking sequence of a finite number of hexagonally close‐packed layers, it is found that a double hexagonal close‐packed stacking sequence is present in the colloidal crystal grain. This analysis method opens up ways to obtain crucial structural information from finite‐sized crystalline samples by employing advanced third‐generation X‐ray sources.